STUDI FENOMENOLOGIS TENTANG PERJUANGAN MENJAGA FLOURISHING PADA DOKTER DI RSUD KAB.KEEROM, PAPUA - Rahmatia Rustam; Fx. Wahyu Widiantoro (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
This study explores the psychological dynamics of physicians serving in the border region of Indonesia, specifically at Keerom Hospital in Papua. Physicians in peripheral areas face a dual workload that encompasses medical occupational risks as well as emotional stress resulting from limited facilities and geographical barriers. This study aims to understand how emotional exhaustion is experienced by these physicians and how they strive toward flourishing amidst such limitations. Utilizing a qualitative approach with Interpretative Phenomenological Analysis (IPA), data were collected through light shadowing observations and in-depth interviews with four physicians (N = 4) who have served for at least two years in Papua. The results identified five main superordinate themes: (1) Emotional Numbing mechanisms as a coping strategy against secondary trauma; (2) Systemic Dual Frustration stemming from the gap between competence and available facilities; (3) Identity Shifting as an effort to separate professional and personal roles; (4) Transcendental Meaning-Making through the spiritualization of their service; and (5) Communal Flourishing derived from the genuine appreciation of the local community. The findings indicate that flourishing among physicians in extreme regions does not result from the absence of stressors, but rather from the ability to transform the meaning of their service. This study recommends the need for a mental support system based on spiritual and relational values for medical personnel in remote areas. ABSTRAK Penelitian ini mengeksplorasi dinamika psikologis dokter yang bertugas di wilayah perbatasan Indonesia, tepatnya di RSUD Kab. Keeroom, Papua. Para dokter di wilayah perifer menghadapi beban kerja ganda yang mencakup risiko okupasional medis serta tekanan emosional akibat keterbatasan fasilitas dan hambatan geografis. Penelitian ini bertujuan untuk memahami bagaimana kelelahan emosional (emotional exhaustion) dihayati oleh para dokter dan bagaimana mereka mengupayakan kondisi flourishing (kebermekaran jiwa) di tengah keterbatasan tersebut. Menggunakan pendekatan kualitatif dengan metode Interpretative Phenomenological Analysis (IPA), data dikumpulkan melalui observasi shadowing ringan dan wawancara mendalam terhadap empat dokter (N=4) yang telah bertugas minimal dua tahun di Papua. Hasil penelitian mengidentifikasi lima tema induk utama: (1) Mekanisme Emotional Numbing sebagai strategi bertahan dari trauma sekunder; (2) Frustrasi Ganda Sistemik akibat kesenjangan antara kompetensi dan fasilitas; (3) Identity Shifting sebagai upaya memisahkan peran profesional dan personal; (4) Transcendental Meaning-Making melalui spiritualisasi tugas pengabdian; dan (5) Communal Flourishing yang bersumber dari apresiasi tulus masyarakat lokal. Temuan menunjukkan bahwa flourishing pada dokter di wilayah ekstrem bukan dihasilkan dari ketiadaan stresor, melainkan dari kemampuan melakukan transformasi makna terhadap pengabdian mereka. Penelitian ini merekomendasikan perlunya sistem dukungan mental yang berbasis pada nilai-nilai spiritual dan relasional bagi tenaga medis di daerah terpencil.